Preparation method of alpha-Fe2O3 / Bi2MoO6atFe-based metal wire mesh supported photocatalysis mesh
By using a wire mesh as a support, the Bi2MoO6 catalyst is solidly supported to form an α-Fe2O3/Bi2MoO6@Fe wire mesh-loaded photocatalytic network, which solves the problems of low mechanical strength and poor corrosion resistance of traditional support, and achieves multiple reuses of the catalyst and improves the photocatalytic performance.
Patent Information
- Application Number
- CN202411982430.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
Existing photocatalyst carriers, such as shells, fibers and foam sponges, have low mechanical strength, low stiffness and poor corrosion resistance, making it difficult to achieve long-term large-scale applications for many long periods.
A wire mesh is used as the support for the photocatalyst, and a mesh-shaped support with an α-Fe2O3 shell is formed through the steps of acid-base corrosion pretreatment, drying and calcining, and a Bi2MoO6 catalyst is solidly supported by solvent thermal method to form an α-Fe2O3/Bi2MoO6@Fe wire mesh-supported photocatalytic network.
The multiple repeated recovery and use of the catalyst is achieved, the mechanical strength and corrosion resistance of the photocatalyst are improved, the separation and transmission capabilities of photogenerated carriers are enhanced, and the photocatalytic performance is significantly improved.
Smart Images

Figure CN119819316A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of photocatalysts, and in particular to a method for preparing an alpha-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh-loaded photocatalytic mesh. Background technology:
[0002] Bismuth molybdate is made from [Bi2O2] 2+ It is connected with the corner-sharing structure of the MoO6 octahedron, giving it a unique layered structure, which has attracted widespread attention from scholars in the field of photocatalytic degradation of organic matter. Combining Bi2MoO6 with a functional carrier can not only stabilize the load but also produce a synergistic effect to promote the catalytic reaction. At present, some scholars have fixed the photocatalyst powder on carriers such as shells, fibers and foam sponges by deposition, spraying or using polymer cross-linking agents to achieve the recovery of powdered catalysts. However, carriers such as shells, fibers and foam sponges have low mechanical strength, low rigidity and poor corrosion resistance, which makes it impossible for the catalyst to be repeatedly used on a large scale for a long time.
[0003] Metal mesh materials are a new type of multifunctional materials that have emerged in recent years with the rapid development of material preparation and mechanical processing technology. They have many advantages such as high mechanical strength, high rigidity, corrosion resistance, easy preparation, and low cost. Metal mesh has good corrosion resistance and wear resistance, can withstand high reaction conditions such as high temperature and high pressure, is not easily destroyed, and has good carrier stability. At the same time, the surface area of the wire mesh is large, which can increase the contact area of the photocatalyst, provide more reaction sites, and enhance the reaction effect. Metal mesh materials have a large amount of designable internal space, which makes it easier to achieve multifunctional integration. In addition, good permeability allows the photocatalyst, reactants and light to fully contact, thereby increasing the reaction rate. Moreover, the metal mesh can be used repeatedly without damage or loss of activity, which can reduce costs and environmental pollution. Therefore, it is used as a carrier of photocatalyst, and the photocatalyst is firmly fixed on the surface of the wire mesh through the solvothermal method. It not only provides a large number of loading sites for the catalyst, but the excellent conductivity of the metal can also promote the transfer of photogenerated electrons and improve the separation efficiency of photogenerated electrons and holes, thereby producing a synergistic effect to improve the performance of the catalyst, and cleverly solves the problem of difficult recovery of catalyst powder. It has broad application prospects as a photocatalyst carrier in photocatalytic technology. Summary of the invention:
[0004] The purpose of the present invention is to provide a method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh-loaded photocatalytic mesh.
[0005] The present invention is implemented by the following technical solutions:
[0006] A method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic mesh comprises the following steps:
[0007] S1: Metal Wire Mesh Pretreatment
[0008] Firstly, acid-base corrosion pretreatment is used to remove grease and impurities on the surface of the 304 metal steel wire mesh, then drying is performed, and finally calcination is performed to obtain a mesh carrier with an α-Fe2O3 shell layer;
[0009] S2: Preparation of precursor solution
[0010] Dissolve Bi(NO3)3·5H2O, Na2MoO4·2H2O and surfactant in solvents respectively and then mix and stir to obtain a precursor solution;
[0011] S3: Reaction
[0012] The precursor solution and the mesh carrier are placed in a reaction kettle, the precursor solution covers the mesh carrier, and after reacting at 130-190°C for 6-8 hours, the reaction is carried out by washing and drying to obtain an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh-loaded photocatalytic mesh.
[0013] Furthermore, the S1 comprises the following steps:
[0014] S1-1: Soak a 304 metal steel wire mesh in ultrapure water, 95% anhydrous ethanol solution, and 40 mL / L dilute nitric acid solution and 1% NaOH solution for 10 minutes respectively, and then remove the mesh to obtain a first wire mesh;
[0015] S1-2: drying the first screen at a temperature of 40-80° C. for a time of 8-24 hours to obtain a second screen;
[0016] S1-3: calcining the second wire mesh at 400-800° C. for 2-6 h, and then annealing naturally to obtain a mesh carrier.
[0017] Furthermore, in S2, the molar ratio of Bi(NO3)3·5H2O, Na2MoO4·2H2O, and surfactant is (1-4):(1-4):(1-6).
[0018] Furthermore, in S2, the molar ratio of Bi(NO3)3·5H2O, Na2MoO4·2H2O, and surfactant is 4:2:1.
[0019] Furthermore, the solvents used for Bi(NO3)3·5H2O and Na2MoO4·2H2O are ethylene glycol solution, water or anhydrous ethanol solution.
[0020] Furthermore, the surfactant is CTAB or PVP, and the surfactant is dissolved in anhydrous ethanol.
[0021] The advantages of the present invention are: the metal mesh has the characteristics of high mechanical strength, high rigidity and corrosion resistance. The metal mesh carrying Bi2MoO6 catalyst has the characteristics of high temperature resistance, pressure resistance and not easy to be damaged, so it can be recycled and reused many times. α-Fe2O3 is formed in situ on the surface of the metal mesh by high-temperature calcination. α-Fe2O3 can form a heterojunction with the Bi2MoO6 catalyst, effectively enhancing the separation and transmission capabilities of photogenerated carriers, and can greatly improve the photocatalytic ability, which is helpful to improve the photocatalytic performance of the photocatalytic mesh. Description of the drawings:
[0022] Figure 1 This is the morphology of the α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh loaded photocatalytic mesh.
[0023] Figure 2 This is the catalyst energy spectrum of α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic mesh surface.
[0024] Figure 3 This is the cross-sectional energy spectrum of α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic network.
[0025] Figure 4 Infrared spectra of Bi2MoO6 and α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh.
[0026] Figure 5 (a) and (b) are the transient photocurrent response spectra and EIS impedance spectra of Bi2MoO6 powder catalyst and α-Fe2O3 / Bi2MoO6@304 stainless steel wire mesh, respectively. Specific implementation method:
[0027] Example 1: A method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic mesh, comprising the following steps:
[0028] S1: Metal Wire Mesh Pretreatment
[0029] First, acid-base corrosion pretreatment is used to remove grease and impurities on the surface of the 304 metal steel wire mesh, then drying is performed, and finally calcination is performed to obtain a mesh carrier with an α-Fe2O3 shell layer; S1 includes the following steps:
[0030] S1-1: Soak a 304 metal steel wire mesh in ultrapure water, 95% anhydrous ethanol solution, and 40 mL / L dilute nitric acid solution and 1% NaOH solution for 10 minutes respectively, and then remove the mesh to obtain a first wire mesh;
[0031] S1-2: drying the first screen at a temperature of 40° C. for 24 hours to obtain a second screen;
[0032] S1-3: The second wire mesh was calcined at 400° C. for 6 h, and then naturally annealed to obtain a mesh carrier.
[0033] S2: Preparation of precursor solution
[0034] Bi(NO3)3·5H2O, Na2MoO4·2H2O and a surfactant are dissolved in solvents respectively and then mixed and stirred to obtain a precursor solution; the solvents used for Bi(NO3)3·5H2O and Na2MoO4·2H2O are both anhydrous ethanol solutions; the surfactant is CTAB (hexadecyltrimethylammonium bromide), and the surfactant is dissolved in anhydrous ethanol.
[0035] Among them, the molar ratio of Bi(NO3)3·5H2O, Na2MoO4·2H2O and surfactant is 1:1:1.
[0036] S3: Reaction
[0037] The precursor solution and the mesh carrier were placed in a reaction kettle, the precursor solution covered the mesh carrier, and after reacting at 130°C for 18 hours, the reaction was carried out by washing and drying to obtain an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh-loaded photocatalytic mesh.
[0038] Example 2: A method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic mesh, comprising the following steps:
[0039] S1: Metal Wire Mesh Pretreatment
[0040] First, acid-base corrosion pretreatment is used to remove grease and impurities on the surface of the 304 metal steel wire mesh, then drying is performed, and finally calcination is performed to obtain a mesh carrier with an α-Fe2O3 shell layer; S1 includes the following steps:
[0041] S1-1: Soak a 304 metal steel wire mesh in ultrapure water, 95% anhydrous ethanol solution, and 40 mL / L dilute nitric acid solution and 1% NaOH solution for 10 minutes respectively, and then remove the mesh to obtain a first wire mesh;
[0042] S1-2: drying the first screen at a temperature of 80° C. for 8 hours to obtain a second screen;
[0043] S1-3: The second wire mesh was calcined at 800° C. for 2 h, and then naturally annealed to obtain a mesh carrier.
[0044] S2: Preparation of precursor solution
[0045] Dissolve Bi(NO3)3·5H2O, Na2MoO4·2H2O and surfactant in solvents respectively and then mix and stir to obtain a precursor solution;
[0046] The molar ratio of Bi(NO3)3·5H2O, Na2MoO4·2H2O and surfactant is 4:2:6. The solvent used for Bi(NO3)3·5H2O and Na2MoO4·2H2O is water, the surfactant is PVP (polyvinyl pyrrolidone), and the surfactant is dissolved in anhydrous ethanol.
[0047] S3: Reaction
[0048] The precursor solution and the mesh carrier are placed in a reaction kettle, the precursor solution covers the mesh carrier, and after reacting at 190°C for 8 hours, the reaction is carried out by washing and drying to obtain an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh-loaded photocatalytic mesh.
[0049] Example 3: A method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic mesh, characterized in that it comprises the following steps:
[0050] S1: Metal Wire Mesh Pretreatment
[0051] First, acid-base corrosion pretreatment is used to remove grease and impurities on the surface of the 304 metal steel wire mesh, then drying is performed, and finally calcination is performed to obtain a mesh carrier with an α-Fe2O3 shell layer; S1 includes the following steps:
[0052] S1-1: Soak a 304 metal steel wire mesh in ultrapure water, 95% anhydrous ethanol solution, and 40 mL / L dilute nitric acid solution and 1% NaOH solution for 10 minutes respectively, and then remove the mesh to obtain a first wire mesh;
[0053] S1-2: drying the first screen at a temperature of 50° C. for 16 hours to obtain a second screen;
[0054] S1-3: The second wire mesh was calcined at 500° C. for 3 h, and then naturally annealed to obtain a mesh carrier.
[0055] S2: Preparation of precursor solution
[0056] Dissolve Bi(NO3)3·5H2O, Na2MoO4·2H2O and surfactant in solvents respectively and then mix and stir to obtain a precursor solution;
[0057] Among them, in S2, the molar ratio of Bi(NO3)3·5H2O, Na2MoO4·2H2O and surfactant is 4:2:1.
[0058] The solvent used for Bi(NO3)3·5H2O and Na2MoO4·2H2O is ethylene glycol solution; the surfactant is CTAB, and the surfactant is dissolved in anhydrous ethanol.
[0059] S3: Reaction
[0060] The precursor solution and mesh carrier were placed in a reaction kettle, the precursor solution covered the mesh carrier, and reacted at 150°C for 12 hours, followed by washing and drying to obtain an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh-supported photocatalytic mesh. The morphology of the α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh-supported photocatalytic mesh is shown in the figure. Figure 1 As shown in Figure 1, the flower-shaped Bi2MoO6 is evenly distributed on the 304 metal steel wire mesh without agglomeration and is firmly loaded. The energy spectrum of the surface catalyst and the cross-sectional energy spectrum are shown in Figure 1. Figure 2 and Figure 3 As shown, Figure 2 The Bi2MoO6 ball particles are composed of Bi, O, and Mo elements, proving that pure Bi2MoO6 catalyst was synthesized on the surface of 304 metal steel wire mesh. Figure 3 The mid-section energy spectrum is composed of six elements, namely Fe, Cr, Ni, Bi, O, and Mo, which correspond to the elemental composition of Bi2MoO6 and 304 metal steel wire mesh, respectively, proving that there are no other impurities on the surface of the α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh-loaded photocatalytic mesh.
[0061] Figure 4 FT-IR spectrum of Bi2MoO6 particles and α-Fe2O3 / Bi2MoO6@Fe-based metal mesh, located at 556 cm -1 and 728cm -1 The characteristic absorption peak at 596 cm can be attributed to the stretching vibration of Bi-O bond and Mo-O bond; -1 and 1076cm -1 The characteristic peaks nearby are attributed to the stretching vibration peaks of Fe-O bonds, proving that the 304 metal wire mesh forms an α-Fe2O3 shell after high-temperature calcination.
[0062] Figure 5 (a) It can be clearly observed that the transient photocurrent response is significantly enhanced after the catalyst is loaded onto the metal mesh, which means that the photocatalytic mesh has a higher photogenerated electron-hole separation efficiency and higher electron mobility, which is beneficial to the improvement of photocatalytic activity. Figure 5(b) The interfacial charge transfer resistance in the sample was tested by EIS Nyquist. It can be seen that the arc radius was significantly shortened, indicating that the charge separation was significantly enhanced after the α-Fe2O3 / Bi2MoO6 heterojunction was formed on the 304SS surface, the charge transfer resistance was effectively reduced, and the carrier transport was effectively promoted.
[0063] Comparative Example 1: The precursor solution and fiber web prepared by S2 in Example 3 were placed in a reaction kettle, the precursor solution covered the mesh carrier, reacted at 150°C for 12 hours, and then washed and dried to obtain a Bi2MoO6-loaded fiber web.
[0064] Comparative Example 2: The precursor solution prepared by S2 in Example 3 and shell biochar are placed in a reactor, stirred evenly to make the shell biochar evenly dispersed in the precursor solution, reacted at 150°C for 12 hours, washed and dried to obtain a shell biochar / Bi2MoO6 supported composite catalyst.
[0065] Comparative Example 3: The precursor solution prepared by S2 in Example 3 and the cut foam sponge are placed in a reaction kettle, the precursor solution covers the foam sponge carrier, and after reacting at 130°C for 18 hours, the mixture is washed and dried to obtain a Bi2MoO6-loaded foam sponge.
[0066] The wastewater to be treated is antibiotic wastewater containing ciprofloxacin (CIP). The α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh-loaded photocatalytic nets obtained in Examples 1 to 3, the Bi2MoO6-loaded fiber nets obtained in Comparative Example 1, the shell biochar / Bi2MoO6-loaded composite catalyst obtained in Comparative Example 2, and the Bi2MoO6-loaded foam sponge obtained in Comparative Example 3 were used to perform photocatalytic reactions on equal amounts of wastewater to be treated under the same conditions for 3 hours. The wastewater indicators obtained are shown in the following table:
[0067]
[0068] Comparative analysis of the wastewater indicators after treatment in comparative examples 1 to 3 and those after treatment in application examples 1 to 3 shows that the absorbance and TOC content of the wastewater after treatment in embodiments 1 to 3 are lower than the corresponding indicators in comparative examples 1 to 3, while the degradation efficiency and the degradation efficiency after repeated use for five times are significantly higher than the degradation efficiency of comparative examples 1 to 3. Obviously, the catalysts in embodiments 1 to 3 can form a heterojunction with the Bi2MoO6 catalyst through α-Fe2O3 on the surface of the wire mesh, which has a synergistic effect, can improve the degradation efficiency and mineralization rate of ciprofloxacin, an organic pollutant in antibiotic wastewater, and have good cycle stability and reusability.
[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic mesh, characterized in that: It includes the following steps: S1: Metal Wire Mesh Pretreatment Firstly, the grease and impurities on the surface of the Fe-based metal steel mesh are removed by acid-base corrosion pretreatment, then dried, and finally calcined to obtain a mesh carrier with an α-Fe2O3 shell layer; S2: Preparation of precursor solution Dissolve Bi(NO3)3·5H2O, Na2MoO4·2H2O and surfactant in solvents respectively and then mix and stir to obtain a precursor solution; S3: Reaction The precursor solution and the mesh carrier are placed in a reaction kettle, the precursor solution covers the mesh carrier, and after reacting at 130-190° C. for 6-18 hours, the reaction is performed by washing and drying to obtain an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh-loaded photocatalytic mesh.
2. The method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic network according to claim 1, characterized in that: The S1 comprises the following steps: S1-1: Soak the 304 metal steel wire mesh in ultrapure water, 95% anhydrous ethanol solution, and 40 mL / L dilute nitric acid solution 1% NaOH solution for 10 minutes respectively, and then remove the mesh to obtain the first wire mesh; S1-2: drying the first screen at a temperature of 40-80° C. for a time of 8-24 hours to obtain a second screen; S1-3: calcining the second wire mesh at 400-800° C. for 2-6 h, and then annealing naturally to obtain a mesh carrier.
3. The method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic network according to claim 1, characterized in that: In S2, the molar ratio of Bi(NO3)3·5H2O, Na2MoO4·2H2O, and surfactant is (1-4):(1-4):(1-6).
4. The method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic network according to claim 3, characterized in that: In S2, the molar ratio of Bi(NO3)3·5H2O, Na2MoO4·2H2O, and surfactant is 4:2:
1.
5. The method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic mesh according to claim 1, characterized in that: In S2, the solvents used for Bi(NO3)3·5H2O and Na2MoO4·2H2O are ethylene glycol solution, water or anhydrous ethanol solution.
6. The method for preparing an α-Fe2O3 / Bi2MoO6@Fe-based metal wire mesh supported photocatalytic mesh according to claim 1, characterized in that: In S2, the surfactant is CTAB or PVP, and the surfactant is dissolved in anhydrous ethanol.
Citation Information
Patent Citations
Preparation method and application of photocatalytic material with BiOBr loaded on stainless steel wire mesh
CN112371142A
Bismuth molybdate heterojunction catalyst and preparation method and application thereof
CN115069236A